2016
DOI: 10.1007/s00438-016-1279-8
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and functional analysis of S-RNase involved in the self-incompatibility of citrus

Abstract: S-RNase-based self-incompatibility is found in Solanaceae, Rosaceae, and Scrophulariaceae, and is the most widespread mechanism that prevents self-fertilization in plants. Although 'Shatian' pummelo (Citrus grandis), a traditional cultivated variety, possesses the self-incompatible trait, the role of S-RNases in the self-incompatibility of 'Shatian' pummelo is poorly understood. To identify genes associated with self-incompatibility in citrus, we identified 16 genes encoding homologs of ribonucleases in the ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 71 publications
2
25
0
Order By: Relevance
“…Some T2 RNase genes in citrus are reportedly involved in fruit development (Liang et al, 2017). Liang et al (2017) found that one gene (CsRNS1) out of nine T2 RNase genes was continuously up-regulated in sweet orange fruit from flowering to 240 d after flowering, suggesting that the S-like RNase genes obtained here may be involved in fruit development. However, none of the T2 RNase genes isolated in this study were expressed in fruit tissues, indicating that their function is not associated with fruit development.…”
Section: Tissue-specific Expressionmentioning
confidence: 64%
See 3 more Smart Citations
“…Some T2 RNase genes in citrus are reportedly involved in fruit development (Liang et al, 2017). Liang et al (2017) found that one gene (CsRNS1) out of nine T2 RNase genes was continuously up-regulated in sweet orange fruit from flowering to 240 d after flowering, suggesting that the S-like RNase genes obtained here may be involved in fruit development. However, none of the T2 RNase genes isolated in this study were expressed in fruit tissues, indicating that their function is not associated with fruit development.…”
Section: Tissue-specific Expressionmentioning
confidence: 64%
“…Six and seven genes annotated as ribonuclease T2 genes were identified from the sweet orange and clementine genome databases, respectively, using database searches (Table 3). Liang et al (2017) used a similar approach to obtain T2 RNase genes by surveying different databases from those used in this study; they obtained seven and nine T2 RNase genes from the clementine v.1.0 and sweet orange v.2.0 databases, respectively. In this study, obtained amino acid sequences were queried using a tblastx search of the EST database that resulted in five hits.…”
Section: Database Search Construction Of Phylogenetic Trees and Isomentioning
confidence: 99%
See 2 more Smart Citations
“…An increasing number of studies have recently focused on the SI mechanism in Citrus . Comparative transcriptome approaches have been applied in order to identify proteins putatively involved in the SI response; however, only in C. grandis L. Osbeck (pummelo), an S-RNase gene (homolog to those of Rosaceae and Solanaceae) has been identified, whose product was able to inhibit pollen tube growth ( Liang et al., 2017 ). Recently, the S-RNase-based SI system was verified in pummelo, and S-RNases were confirmed to be the pistil S determinants ( Liang et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%